MANFAAT JEJARING SOSIAL BAGI KEGIATAN DAKWAH SISWA PRATEPSASANA ISMAIL MEMORIAL SCHOOL (PIMS) NAKHON SI THAMMARAT THAILAND SELATAN - Maya Rini Handayani (Wahana Akademika: Jurnal Studi Islam dan Sosial, 2014)
AbstractThis article discusses about the benefits of information technology for Islamicda’wa activities of PIMS (Pratepsasana Ismail Memorial School) students. In thisarticle, the information technology focuses on social network, which is a facebook. PIMS is a school managed by Pondok Bantan in Nakhon Si Thammarat(NST) province, Southern Thailand. Both PIMS school and pondok Bantanhave provided some modern facilities such as buildings, classrooms, and computer laboratories. Therefore, it is very interesting to know the PIMS student’sIslamic da’wa activities using the information technology by utilizing computerlaboratories in PIMS and Pondok Bantan.Keyword: dakwah Islamiyah, facebook, Pratepsasana Ismail MemorialSchool